2019
DOI: 10.1155/2019/5879714
|View full text |Cite
|
Sign up to set email alerts
|

MTOR-Mediated Autophagy Is Involved in the Protective Effect of Ketamine on Allergic Airway Inflammation

Abstract: Unresolved inflammation underpins the pathogenesis of allergic airway diseases, such as asthma. Ketamine, accepted as a promising therapy for resistant asthma, has been demonstrated to attenuate allergic airway inflammation. However, the anti-inflammatory mechanism by ketamine in this setting is largely unknown. We aimed to investigate whether autophagy was involved in the protective effect of ketamine on allergic airway inflammation. Female C57BL/6 mice were sensitized to ovalbumin (OVA) and treated with keta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The ratio of lc3-ii to lc3-i is commonly used to analyze autophagic activity, of which Beclin-1 is also considered a hallmark (17). Furthermore, it has been reported that autophagy suppression may inhibit airway inflammation in allergic mice (16). Therefore, the present study assessed whether eX-527 exerted anti-inflammatory effects by suppressing autophagy.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…The ratio of lc3-ii to lc3-i is commonly used to analyze autophagic activity, of which Beclin-1 is also considered a hallmark (17). Furthermore, it has been reported that autophagy suppression may inhibit airway inflammation in allergic mice (16). Therefore, the present study assessed whether eX-527 exerted anti-inflammatory effects by suppressing autophagy.…”
Section: Resultsmentioning
confidence: 97%
“…mTOR activation has been shown to reduce inflammation in an oVa-induced allergic mouse model (16) and autophagy is known to be controlled by the mTor signaling pathway (19). Furthermore, mTor levels were decreased in the lungs of allergic mice, whereas mTor activation inhibited allergic airway inflammation via suppressed autophagy (16). Therefore, mTor could represent a pivotal modulator of asthma development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations